Comparison of Lower Limb Kinematics Between Increased Hip Flexion Gait and Cycling: Implications for Exercise Prescription in Clinical Populations - Nuno Oliveira; Tanner Thorsen (Applied Sciences)
Exercise is an important component in the treatment and improvement of function in populations with or at risk of lower limb injury. Cycling is the most common exercise modality used by these populations. However, reduced lower limb joint excursion and/or range of motion (ROM) during cycling might limit the optimization of functional improvements. Increased hip flexion gait (HFgait) is a new exercise modality that might result in larger lower limb joint excursions compared to cycling. The purpose of this study was to compare lower limb kinematics between HFgait and cycling. Twelve healthy individuals participated in the study. Each participant performed cycling and HFgait. Hip, knee, and ankle kinematics in the sagittal, frontal, and transverse planes were analyzed with and without phase offset reduction (POR). Discrete and continuous analyses were performed. Discrete analysis indicated differences for at least one of the variables analyzed (maximum, minimum, and ROM) for the hip (p ≤ 0.041), knee (p ≤ 0.008), and ankle (p ≤ 0.040) across all planes. For the continuous analysis, differences between HFgait and cycling kinematics were observed during the cycles for the hip, knee, and ankle sagittal (hip: original: 85%; with POR: 77%; knee: original: 93%; with POR: 76%; ankle: original: 14%; with POR: 14%), frontal (hip: original: 93%; with POR: 98%; knee: original: 41%; with POR: 12%; ankle: original: 4%; with POR: 5%), and transverse (hip: original: 66%; with POR: 0%; knee: original: 14%; with POR: 0%; ankle: original: 3%; with POR: 0%) planes. HFgait resulted in larger hip (+60.2°) and knee (+38.2°) sagittal plane ROM while maintaining the hip in a more neutral position in the frontal plane compared with cycling. These findings can support the development of rehabilitation strategies with the goal of improving function and joint range of motion while also receiving the health benefits of exercise.